Territory Molluss Gelmint Larvae, Distribution And Morpho-Biological Properties - Rustamova L.Q; Murodova.X.Z (Genius Publishing Group, 2022)
This article discusses the morphology of Tamerlania zarudnyi sercarium and helminth larvae developing in the presence of terrestrial mollusks in the Fergana Valley, the taxonomic composition of the species, the intermediate host and the degree of infestation with larvae, species distribution and ecology, as well as research methods used to identify this species. and methods are described
Keywords: Helminth; larva; fauna; biotope